1995
DOI: 10.1007/s001250050337
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal insulin therapy: the clinical realities

Abstract: Summary To evaluate metabolic control and safety parameters (hypoglycaemia frequency and nasal mucosa physiology), 31 insulin-dependent diabetic patients were treated with intranasal insulin at mealtimes for i month and with subcutaneous fast-acting insulin at meals for another month in an open, crossover randomized trial. During both treatment periods the patients were treated with intermediate-acting insulin at bedtime. Six of the patients were withdrawn from the study during intranasal insulin therapy due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Clinical studies in patients with Type 1 and Type 2 diabetes have revealed a rapid but relatively short‐lived increase in plasma insulin following nasal administration with multiple doses required to control postprandial hyperglycaemia [66,67]. However, metabolic control was frequently inferior to s.c. insulin and many patients suffered local nasal irritation [67–69]. More recently, a lyophilized nasal insulin preparation containing sodium glycocholate given preprandially achieved glycaemic control equivalent to a regimen of twice daily NPH insulin in patients with Type 2 diabetes over a 4‐month period [70].…”
Section: Intranasal Deliverymentioning
confidence: 99%
“…Clinical studies in patients with Type 1 and Type 2 diabetes have revealed a rapid but relatively short‐lived increase in plasma insulin following nasal administration with multiple doses required to control postprandial hyperglycaemia [66,67]. However, metabolic control was frequently inferior to s.c. insulin and many patients suffered local nasal irritation [67–69]. More recently, a lyophilized nasal insulin preparation containing sodium glycocholate given preprandially achieved glycaemic control equivalent to a regimen of twice daily NPH insulin in patients with Type 2 diabetes over a 4‐month period [70].…”
Section: Intranasal Deliverymentioning
confidence: 99%
“…Owing to the high molecular weight of the insulin peptide and the lack of lipophilicity, insulin poorly crosses the cell membranes, if administered to the mucosal membranes without absorption adjuvants. These characteristics also make nasal insulin a poor candidate for the treatment of patients with type 1 diabetes 6–8. Meaningful metabolic effects are recognised after intranasal insulin administration only if absorption enhancers are used, and even then large doses are required 9.…”
Section: Introductionmentioning
confidence: 99%
“…Since the early days of insulin therapy, alternative routes of insulin administration have been investigated in attempts to overcome these limitations (Olsen et al, 1994). As an example, nasal delivery of insulin has been extensively studied, but the bioeffectiveness, is poor, and the nasal mucosa may be irritated by repeated intranasal insulin administration (Hilsted et al, 1995).…”
Section: Introductionmentioning
confidence: 99%